Models Of Good School Governance - Fajriana; Siraj (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
School administration should focus on improving oriented performance in terms of policies and procedures that will be implemented in schools. the principle of good school governance that mediates various interests to reach a broad consensus about what is in the best interest of the school community regarding policies and procedures. The purpose of this research is focused on efforts to produce a picture of the potential, implementation and analysis of the implementation of consensus-oriented vocational education so as to produce quality graduates. The results of this study are: 1) analysis of the implementation of good school governance in vocational schools; 2) analysis of supporting and inhibiting factors for the implementation of good school governance in vocational schools; and 3) good school governance model design in vocational schools. This research is a qualitative research with a naturalistic phenomenological approach, with a case study research design. The subjects in this study were school principals, teachers, DU/DI parties, stakeholders and the community. The research object is an analysis of the good school governance model at SMK Negeri 4 Lhokseumawe. Data collection techniques using interviews, observation and documentation. Data analysis was carried out through individual case and cross case analysis. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The importance of this research is to be able to produce a recommendation that is more objective and applicable so that it is useful as a significant input in the framework of overcoming the problem of unemployment for vocational high school graduates in Lhokseumawe City. The contribution of this research is to produce a recommendation model for the implementation of consensus-based vocational schools as a key factor in the success of good school governance. Good school governance is a management model that is appropriate to be applied in the management of Vocational High Schools. Good school governance as a management model that provides greater autonomy to schools and encourages participatory decision-making that directly involves all school members (teachers, students, principals, education staff, parents of students) even the business and industrial world, as well as society as a whole wider.